Molecular taxonomy of scopulariopsis-like fungi with description of new clinical and environmental species. Issue 4 (April 2016) - Jagielski, Tomasz; Sandoval-Denis, Marcelo; Yu, Jin; Yao, Limin; Bakuła, Zofia; Kalita, Joanna; Skóra, Magdalena; Krzyściak, Paweł; de Hoog, G. Sybren; Guarro, Josep; Gené, Josepa
Abstract: The taxonomy of scopulariopsis-like fungi, comprising numerous human opportunistic species, has recently been reassessed with delineation of the genera Microascus, Pithoascus, Pseudoscopulariopsis, and Scopulariopsis, using morphological data and multilocus sequence analysis based on four loci (ITS, LSU, EF-1α, and TUB ). In this study, the same genetic markers were used to investigate a set of clinical and environmental isolates, morphologically identified as Microascus and Scopulariopsis spp. The ingroups of the concatenated phylogenetic tree resolved 41 species clades, with isolates distributed in four main lineages corresponding to the genera Microascus, Pithoascus, Scopulariopsis, and newly established genus Fuscoannellis, typified by Scopulariopsis carbonaria . The new species Microascus chinensis, Microascus onychoides, Microascus pseudolongirostris, Pithoascus lunatus, and Scopulariopsis macurae were described. Microascus trigonosporus var. terreus and Scopulariopsis alboflavescens were found different from M. trigonosporus and Scopulariopsis brevicaulis, respectively. All the species identified in the study, except Fuscoannellis carbonaria and S. macurae, originated from clinical samples, suggesting their potential role in human disease. The use of a four marker combination was demonstrated an efficient and reliable approach to infer phylogenetic relationships among the scopulariopsis-like fungi. Yet, the only genetic marker able to discriminate all species was EF-1α, therefore proposed as a secondary barcode for the identification of these fungi.